2018
DOI: 10.15621/ijphy/2018/v5i4/175694
|View full text |Cite
|
Sign up to set email alerts
|

Scapular Dyskinesis in Asymptomatic Water Polo Players: Does Prehabilitation Prevent Negative Outcomes?

Abstract: Background: Scapular dyskinesis, or abnormal scapular dynamic control, is a condition which is associated with athletes presenting with shoulder pathology, although it is also found in asymptomatic individuals. Studies differ on whether it is a cause or a symptom of shoulder pain. There is currently no research on whether treating scapular dyskinesis prior to the onset of pain by prehabilitation will stop the progression of pain in asymptomatic water polo players.Methods: This study was a prospective randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…There is considerable discussion in the literature regarding the presence of SD among overhead athletes with or without symptoms, as well as the presence of SD being a potential risk factor for sustaining injury in the future. 8,9,31,32,37 The current findings from the current study support the high incidence of SD among athletes with shoulder symptoms. However, it is important to note that only three studies with a total of 68 individuals investigated the presence of SD within the symptomatic athlete population while 16 studies with a total of 657 individuals investigating the presence of SD in the asymptomatic athletic population were included.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…There is considerable discussion in the literature regarding the presence of SD among overhead athletes with or without symptoms, as well as the presence of SD being a potential risk factor for sustaining injury in the future. 8,9,31,32,37 The current findings from the current study support the high incidence of SD among athletes with shoulder symptoms. However, it is important to note that only three studies with a total of 68 individuals investigated the presence of SD within the symptomatic athlete population while 16 studies with a total of 657 individuals investigating the presence of SD in the asymptomatic athletic population were included.…”
Section: Discussionsupporting
confidence: 77%
“…Additionally, the JBI tool is specifically designed to give the raters the choice of including or excluding the scored study based on their interpretation of the scoring. Of the included studies, 18 12,[21][22][23][24][25][26][27]32,[37][38][39][40][41]44,45,49,50 addressed the target population appropriately with the sample frame and had adequate sample sizes. However, only 13 studies 12, 19,23,24,26,28,31,32,41,42,47,49,50 reported both the study subjects and setting in detail.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation